Electro Less Duplex Nickel Coating and Tribological Characterization Under Elevated Temperature - Rajarshi Chakraborty; Arka Bhattarcharjee; Sourav Dey; Subhadip Maity; Amrita Pradhan (International Journal of Electro-Mechanics and Material Behaviour, 2023)
Electroless Ni-P (EN) coatings had previously demonstrated their ability to improve the tribological properties of the underlying substantial. This is due to its high hardness, fatigue strength, and chemical resistance. Nevertheless, the EN coverings' effectiveness at high temperatures, as well as their heat resistance, have yet to be evaluated. The current work investigates the tribological properties, namely friction and wear, of EN coatings at increased temperatures (100 ºC, 200 ºC, and 300 ºC), by altering the interfacial testing constraints, namely normal load and sliding speed. Study findings of the tribological properties of the coatings are conducted for heat-treated and as-deposited specimens. The acquired results are contrasted with the results obtained from the coating's ambient temperature (AT) testing. For all treatment temperatures, the friction factor (COF) as well as wear of the EN coating are observed to rise under greater load. Yet, when slide speed varies, all COF and attrition rates exhibit a reversal pattern. The as-deposited specimens have a lower rate of wear, especially at maximum temperatures, that could be attributed to the in-situ thermal processing obtained throughout the experiment.
Keywords: Coating; Electroless Ni-P; Elevated temperature; Friction; Friction coefficient; Wear